Rapid Evolution of Invasive Weeds Under Climate Change: Present Evidence and Future Research Needs - Clements, David R.; Jones, Vanessa L. (Frontiers in Agronomy, 2021)
Although evolution has been often seen as a gradual process through a Darwinian lens, far more rapid evolutionary change has been observed in recent times. Recent examples documenting the potential speed of invasive plant evolution have included: latitudinal flowering clines, life history shifts, or abrupt changes in morphology. The timescales for such observations range from centuries down to less than five years. Invasive weeds provide good models for the rapid changes, partly because invasive weeds exhibit unique evolutionary mechanisms integral to their success. For example, purging of their genetic load may enable invasive plants to adapt more rapidly. Other genetic mechanisms include plasticity as an evolved trait, hybridization, polyploidy, epigenetics, and clonal division of labor. It is well demonstrated that anthropogenic stressors such as habitat disturbance or herbicide use may work synergistically with climate change stressors in fostering rapid weed evolution. Changing temperatures, moisture regimes and extreme climate events operate universally, but invasive plant species are generally better equipped than native plants to adapt. Research on this potential for rapid evolution is critical to developing more proactive management approaches that anticipate new invasive plant ecotypes adapted to changing climatic conditions.